Intestinal gas content and distribution in health and in patients with functional gut symptoms. Issue 9 (21st June 2015) - Bendezú, R. A.; Barba, E.; Burri, E.; Cisternas, D.; Malagelada, C.; Segui, S.; Accarino, A.; Quiroga, S.; Monclus, E.; Navazo, I.; Malagelada, J.‐R.; Azpiroz, F.
Abstract Background The precise relation of intestinal gas to symptoms, particularly abdominal bloating and distension remains incompletely elucidated. Our aim was to define the normal values of intestinal gas volume and distribution and to identify abnormalities in relation to functional‐type symptoms. Methods Abdominal computed tomography scans were evaluated in healthy subjects (n = 37) and in patients in three conditions: basal (when they were feeling well; n = 88), during an episode of abdominal distension (n = 82) and after a challenge diet (n = 24). Intestinal gas content and distribution were measured by an original analysis program. Identification of patients outside the normal range was performed by machine learning techniques (one‐class classifier). Results are expressed as median (IQR) or mean ± SE, as appropriate. Key Results In healthy subjects the gut contained 95 (71, 141) mL gas distributed along the entire lumen. No differences were detected between patients studied under asymptomatic basal conditions and healthy subjects. However, either during a spontaneous bloating episode or once challenged with a flatulogenic diet, luminal gas was found to be increased and/or abnormally distributed in about one‐fourth of the patients. These patients detected outside the normal range by the classifier exhibited a significantly greater number of abnormal features than those within the normal range (3.7 ± 0.4 vs 0.4 ± 0.1; p < 0.001). Conclusions & Inferences The analysis of a large cohort of subjects using original techniques provides unique and heretofore unavailable information on the volume and distribution of intestinal gas in normal conditions and in relation to functional gastrointestinal symptoms.